Effect of cardiolipin on aquaporin Z: a cryo-EM study - Leo, Zhenn Yi (Nanyang Technological University, 2023)
Aquaporins are a family of transmembrane channel proteins responsible for osmoregulation in biological systems. Despite their important physiological role, modulators of aquaporin activity are still not available. An anionic lipid, cardiolipin, was found to stabilize aquaporin Z (AqpZ), an aquaporin found in E. coli, and increase its water permeability. This paper focuses on the cryo-EM structural determination of AqpZ in nanodiscs, with and without added E. coli cardiolipin, to understand the mechanism by which cardiolipin stabilizes and increases the activity of AqpZ. This understanding could facilitate the development of drugs capable of modulating aquaporin activity. Single particle analysis (SPA) of cryo-EM data yielded a 6.3 Å structure of AqpZ in lipid environment. Comparison of this structure with the X-ray crystal structure of AqpZ in octyl glucoside detergent revealed minor structural differences. The resolution of the structure obtained was likely limited due to the high symmetry of the tetrameric molecule resulting in poor alignment of particles during SPA. A fusion protein construct of maltose-binding protein (MBP) and AqpZ was designed to introduce asymmetry to the molecule. The purified protein was shown to tetramerize in mild detergents, indicating that MBP-AqpZ is a suitable candidate for reconstitution into nanodiscs for cryo-EM data collection.